Lado Kralj and Nikola Petković: Opposite Approaches to Humor and the Abject - Badurina, Natka (Poznańskie Studia Slawistyczne, 2025)
The article provides an analysis of two novels, one Slovenian, Ne bom se več drsal na bajerju by Lado Kralj (2022), and one Croatian, Put u Gonars by Nikola Petković (2018), with a special focus on the theme of borders. Both novels deal with the period of the Italian occupation of Yugoslav lands. In the interpretation, the border is understood in three ways: first, in the spatial sense, then as a boundary in relation to the abject (in the sense of Julia Kristeva), and finally as the implicit author’s ideological and ethical principle. The article highlights the differences between the two novels in the use of disgust as a motif, the (lack of) responsibility towards history, and the depiction of the relations between warring sides and ideologies. In line with the literary studies of memory, the analysis aims to contribute to understanding the light in which World War II is remembered in Slovenia and Croatia today, concluding that the memory of the resistance movement in Slovenia has remained an important part of the public sphere even after the 1990s, while in Croatia it has been marginalized and imbued with unease.